A primer for managing international collaboration and legal compliance in biobank based genomics - Klingström, Tomas; Bongcam-Rudloff, Erik; Reichel, Jane (PeerJ Preprints, 2016)
Resolving ethical and legal concerns is a time consuming but rarely insurmountable task when obtaining samples from biobanks. The BBMRI-LPC project has throughout its lifetime resolved numerous such issues and intense communication between involved researchers and experts have been necessary to resolve various issues. To facilitate efficient communication it is useful for non-experts to have an at least basic understanding on how the regulatory system for managing biological samples is constructed to balance the sometimes conflicting needs of privacy, trust and scientific progress. Although laws regulating research oversight have been implemented differently in every country, there is a similarity of core principles founded on international charters. These core principles are based on the concept of consent and actions taken by the biobank in regards to sample usage rely on either an explicit or presumed consent. In interview studies among donors chief concerns among donors are focused on privacy, efficient sample utilization and if donors are given access to information generated from their samples. Despite a lack of clear evidence regarding which concern takes precedent among donors, scientific as well as public discourse has largely focused on privacy concerns and the right of donors to control the usage of their samples. As a result biobank governance has taken a largely negative approach to uncertainties in sample utilization. This mean that sample usage is likely to be restricted if there is any uncertainty if the intended usage is in line with donor expectations. To help biobank professionals avoid making unnecessary mistakes we have developed this basic primer covering the relationship between ethics and law, the concept of informed consent and consideration for returning findings to donors.
Keywords: Ethics; genomics; biobank; law; training; biospecimen; personal data; consent; incidental findings